Pap Smears Cytology of Cervical Abnormalities in Derna, Libya - Srgewa, Amal; Raffalla, Noria (AlQalam Journal of Medical and Applied Sciences, 2024)
The study aimed to provide information about the prevalence of various cervical lesions diagnosed by Papanicolaou smear tests among women in the city of Derna, in eastern Libya. The reporting of the Pap smears is based on the 2014 Bethesda system. The study included seventy-two cervical Pap smears cytology received at the Noor-AL-Huda Medical Center Pathology Laboratory in Derna City, east of Libya, and processed using conventional smear techniques. The data was gathered retrospectively from March 2022 to August 2023. A total of 72 cervical Pap smears were included in the study. The majority of the cases reported were Negative for Intraepithelial Lesions or Malignancy (NILM) 54 (75%). Out of the 72 reports, 2 (2.7%) were unsatisfactory. Low-grade Squamous Intraepithelial Lesions (LSIL) were found in 8 cases (11.11%), and 4 (5.5%) were High-grade Intraepithelial Lesions (HSIL). Atypical Squamous Cells cannot exclude HSIL (ASC-H) were found in 4 cases (5.5%). LSIL and HSIL were more common among women aged 30-40 years. The age of the patients included in this study ranged from 30 to 56, with a mean age of 40 years. These findings emphasize the importance of a well-organized cervical screening program. In particular, women over 30 years should be educated about the importance of Pap smears and encouraged to undergo regular screening. هدف هذه الدراسة تقديم معلومات حول مدى انتشار آفات عنق الرحم المختلفة التي يتم تشخيصها عن طريق اختبارات مسحة عنق الرحم بين النساء في مدينة درنة شرق ليبيا. يعتمد تقرير فحص مسحات عنق الرحم على نظام Bethesda لعام 2014. شملت الدراسة اثنين وسبعين عينة من مسحة عنق الرحم التي تم استلامها في مختبر علم الأمراض بمركز نور الهدى الطبي في مدينة درنة، شرق ليبيا، وتم معالجتها باستخدام تقنيات المسحة التقليدية. وتم جمع البيانات بأثر رجعي من مارس 2022 إلى أغسطس 2023. تم تضمين ما مجموعه 72 مسحة عنق الرحم في الدراسة. كانت غالبية الحالات التي تم فحصها سلبية للآفات داخل الظهارة أو الأورام الخبيثة (NILM) 54 (75٪). من أصل 72 مسحة، كان عدد عينيتين (2.7%) غير مطابقة للمواصفات. تم العثور على آفات حرشفية منخفضة الدرجة داخل الظهارة (LSIL) في 8 حالات (11.11%)، وكانت 4 (5.5%) آفات داخل الظهارة عالية الجودة (HSIL). لا يمكن للخلايا الحرشفية غير النمطية استبعاد وجود HSIL (ASC-H) في 4 حالات (5.5%). كان LSIL وHSIL أكثر شيوعًا بين النساء الذين تتراوح أعمارهم بين 30-40 عامًا. تراوحت أعمار المرضى المشمولين في هذه الدراسة من 30 إلى 56 عامًا، بمتوسط عمر 40 عامًا. تؤكد هذه النتائج على أهمية وجود برنامج جيد التنظيم لفحص عنق الرحم. وعلى وجه الخصوص، ينبغي تثقيف النساء فوق سن 30 عامًا حول أهمية مسحة عنق الرحم وتشجيعهن على الخضوع لفحص منتظم